PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA REGU PENJAGAAN DI LEMBAGA PEMASYARAKATAN KELAS II A KEROBOKAN - I Made Bhaskara Jaya Wardana; Mitro Subroto (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
This research was conducted to determine the influence of leadership style on the motivation of the guard team work in Lembaga Pemasyarakatan Kelas II A Kerobokan. In this study the authors used quantitative research methods with a population of all guarding squads in Lembaga Pemasyarakatan Kelas II A Kerobokan of 58 people. The sampling process in this study uses saturated sample techniques because the entire population in this study is a sample. The results of this study showed that 23.9% of the motivation of the guard squad at Lembaga Pemasyarakatan Kelas II A Kerobokan was influenced by leadership style while the remaining 76.1% was influenced by other models not discussed in this study. This study concluded that leadership style influenced the motivation of the guard team's work at Lembaga Pemasyarakatan Kelas II A Kerobokan.